The assessment of cytotoxic T cell and natural killer cells activity in residents of high and ordinary background radiation areas of Ramsar-Iran - Borzoueisileh, Sajad (Medknow Publications & Media Pvt Ltd, 2013)
The effective radiation dose of human from natural sources is about 2.4 mSv/y and the dose limit for radiation workers is 20 mSv/y. Ramsar, a city in Iran, has been the subject of concern in the last forty years for a high level of radiation measured in some spots as high as 260 mSv/y. Carcinogenesis is one of the most studied effects of radiation especially in high doses. Recent studies showed that the high level of natural radiation received by inhabitants of this area, paradoxically don’t have significant health effect. Natural killer (NK) cells and cytotoxic T cells are the most important cells in tumor immune surveillance and CD107a is a widely expressed intracellular protein located in the lysosomal/endosomal membrane. CD107a transiently located on the cell membrane can be used as a marker of CD8 + T cell degranulation following stimulation. It is also expressed, to a lower extent, on activated NK cells. In this study, 60 healthy people were selected randomly and their consent obtained and confounding factors such as sex, age, life-styles was matched then the count of activated NK and CD8 + cells was compared in high and normal background radiation areas inhabitants of Ramsar. After filling the questionnaire and measurement of background radiation, blood samples of 30 healthy people from each region were analyzed immediately by means of flowcytometry. The leukocytes and their subsets were not significantly different between two groups and the count of active cells was higher in control group. The result shows that the changes in immune system occur due to radiation and maybe it is as a result of higher radiosensitivity of activated cells.